Enzymatic Studies of Isoflavonoids as Selective and Potent Inhibitors of Human Leukocyte 5‐Lipo‐Oxygenase. (28th November 2014) - Mascayano, Carolina; Espinosa, Victoria; Sepúlveda‐Boza, Silvia; Hoobler, Eric K.; Perry, Steve; Diaz, Giovanni; Holman, Theodore R.
<x xml:space="preserve">Abstract</x> Continuing our search to find more potent and selective 5‐LOX inhibitors, we present now the enzymatic evaluation of seventeen isoflavones (IR) and nine isoflavans (HIR), and their in vitro and in cellulo potency against human leukocyte 5‐LOX. Of the 26 compounds tested, 10 isoflavones and 9 isoflavans possessed micromolar potency, but only three were selective against 5‐LOX (IR‐2, HIR‐303, and HIR‐309), with IC50 values at least 10 times lower than those of 12‐LOX, 15‐LOX‐1, and 15‐LOX‐2. Of these three, IR‐2 (6, 7‐dihydroxy‐4‐methoxy‐isoflavone, known as texasin) was the most selective 5‐LOX inhibitor, with over 80‐fold potency difference compared with other isozymes; Steered Molecular Dynamics (SMD) studies supported these findings. The presence of the catechol group on ring A (6, 7‐dihydroxy versus 7, 8‐dihydroxy) correlated with their biological activity, but the reduction of ring C, converting the isoflavones to isoflavans, and the substituent positions on ring B did not affect their potency against 5‐LOX. Two of the most potent/selective inhibitors (HIR‐303 and HIR‐309) were reductive inhibitors and were potent against 5‐LOX in human whole blood, indicating that isoflavans can be potent and selective inhibitors against human leukocyte 5‐LOX in vitro and in cellulo.